Framing and Word Choice in Listening Audio: Analyzing Language Learners' Perceptions - Tania Syafutri; Pahrozi Ahmad; Rezky Atri Oktarin; Ejontomi Afrizon (Universitas Pahlawan Tuanku Tambusai, 2026)
This study emphasizes how crucial it is to comprehend how language generates meaning in listening comprehension. However, the way that word choice and framing in listening materials affect students' views and interpretations of social concerns has received barely any attention in prior research. The impact of word choice and framing on learners' perceptions and interpretations has frequently been ignored in prior study. This study uses Goffman's (1974) theory. A qualitative method was used with 20 college students aged 18-22. Data were collected through listening response tasks, reflective journals, and semi-structured interviews based on an audio about bullying from Listen A Minute, and analysed using thematic analysis across three levels: explanation, interpretation, and description. The results show that word choices provide powerful emotional frames that depict bullies as authoritative characters and victims as psychologically harmed. Pupils tended to believe the story as true and concentrated more on empathy than critical analysis. The study comes to the conclusion that including critical listening techniques is crucial to assisting students in comprehending how language influences ideology, emotion, and social meaning.